"Why are all the Black kids sitting together in the cafeteria?" : and other conversations about race - Tatum, Beverly Daniel (New York : Basic Books, 2003)
With a discussion guide and a new Epilogue by the author, this is the fifth anniversary edition of the bestselling work on the development of racial identity. Shares real-life examples and current research that support the author's recommendations for "straight talk" about racial identity, identifying practices that contribute to self-segregation in childhood groups.
A definition of terms. Defining racism, "Can we talk?" -- The complexity of identity, "Who am I?" -- Understanding blackness in a white context. The early years, "Is my skin brown because I drink chocolate milk?" -- Identity development in adolescence, "Why are all the black kids sitting together in the cafeteria?" -- Racial identity in adulthood, "Still a work in progress ..." -- Understanding whiteness in a white context. The development of white identity, "I'm not ethnic, I'm just normal" -- White identity and affirmative action, "I'm in favor of affirmative action except when it comes to my jobs" -- Beyond black and white. Critical issues in Latino, American Indian, and Asian Pacific American identity development, "There's more than just black and white, you know" -- Identity development in multiracial families, "But don't the children suffer?" -- Breaking the silence. Embracing a cross-racial dialogue, "We were struggling for the words" -- Epilogue 2003: Continuing the conversation -- Appendix. Getting started: a resource guide -- Reader discussion guide.
Originally published: New York : BasicBooks, c1997. With new epilogue by the author.
Includes bibliographical references (p. 269-282) and index.
Keywords: African Americans -- Race identity; White people -- Race identity -- United States; African American children -- Psychology; African American youth -- Psychology; White people -- United States -- Psychology; Race awareness in adolescence -- United States; United States -- Race relations